Virtue, learning, and the Scottish Enlightenment : ideas of scholarship in early modern history - Allan, David (Edinburgh University Press, 1993)
"Virtue, Learning and The Scottish Enlightenment is the latest contribution to a growing reassessment of the moral and intellectual foundations of modern Europe, challenging head-on a number of deeply-rooted assumptions about the basis of both Scottish culture and the Enlightenment. It argues that humanism and Calvinism placed a discussion of the essentially moral function of scholarship at the very centre of historical debate in early modern Scotland, and that this in turn strongly influenced the emergence of an Enlightenment led by the Scottish literati. Introducing the works of more than two hundred scholars and thinkers from the sixteenth to the eighteenth centuries, David Allan explores important - though usually neglected - aspects of the country's intellectual discourse. This pivotal book is both an essential reference tool and a thought-provoking reappraisal of the origins of modern Scotland."--Jacket